2015
DOI: 10.1208/s12248-015-9745-5
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Mixed-Effect Models for Prostate-Specific Antigen Kinetics and Link with Survival in the Context of Metastatic Prostate Cancer: a Comparison by Simulation of Two-Stage and Joint Approaches

Abstract: In metastatic castration-resistant prostate cancer (mCRPC) clinical trials, the assessment of treatment efficacy essentially relies on the time to death and the kinetics of prostate-specific antigen (PSA). Joint modeling has been increasingly used to characterize the relationship between a time to event and a biomarker kinetics, but numerical difficulties often limit this approach to linear models. Here, we evaluated by simulation the capability of a new feature of the Stochastic Approximation Expectation-Maxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…Many recent modeling studies offer thoughtful and detailed analyses of the relationship between PSA dynamics and survival in prostate cancer [25,26,32]; however, these analyses do not consider the exposure-response relationship, only use either simulated data or a previously developed pharmacokinetic model based on pooled data from unrelated, smaller or earlier-phase clinical trials, or are focused on earlier prostate cancer disease states. Our model builds on the previous literature by evaluating the PSA dynamics for an agent targeting androgen biosynthesis for CRPC treatment, a therapeutic strategy that has become increasingly important for this patient population and for which an exposure-survival relationship through PSA dynamics has not been fully described.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent modeling studies offer thoughtful and detailed analyses of the relationship between PSA dynamics and survival in prostate cancer [25,26,32]; however, these analyses do not consider the exposure-response relationship, only use either simulated data or a previously developed pharmacokinetic model based on pooled data from unrelated, smaller or earlier-phase clinical trials, or are focused on earlier prostate cancer disease states. Our model builds on the previous literature by evaluating the PSA dynamics for an agent targeting androgen biosynthesis for CRPC treatment, a therapeutic strategy that has become increasingly important for this patient population and for which an exposure-survival relationship through PSA dynamics has not been fully described.…”
Section: Discussionmentioning
confidence: 99%
“…We developed the tumor size model first (TGI model), estimated ECTS, and then developed the OS model. Joint modeling is theoretically better, as it is estimating model parameters from a joint likelihood that combines uncertainty in parameter estimates . In this work, we therefore did not take into account the uncertainty in ECTS prediction in the OS model.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Desmée, et al32 using a simulation approach showed that joint modeling of PSA kinetics and survival time produces a precise estimation of PSA time-course and survival parameters, compared with two simplified alternatives, two-stage and joint sequential models. They suggested the developed method as a way to improve treatment prediction and evaluation in oncology.…”
Section: Models For Tumor Markers: Examplementioning
confidence: 99%
“…2 depicts a schematic diagram of the model used in the work by Desmée, et al32 In the absence of treatment, it is assumed that prostatic cancer cells, C , proliferate with rate Kprol and eliminate with rate Kd . PSA is produced and secreted with rate Kp and eliminated from the blood with rate Ke .…”
Section: Models For Tumor Markers: Examplementioning
confidence: 99%